Sylvester and the magic pebble [videorecording (DVD)] : and more magical tales - Steig, William, 1907-2003; Fox, Mem, 1946-; Huck, Charlotte S.; Kent, Jack, 1920-1985 (New Video Group, 2005)
In "Sylvester and the magic pebble," a small donkey finds a wishing stone. In "Possum magic, " Grandma Poss needs a certain food for a magical mix that will make Hush visible again. In "Princess Furball," a cruel king intends to marry his daughter to an ogre in exchange for wagons full of silver.